Challenges of Memory: On a Similar Night by Leopoldo Brizuela and Purgatory, by Tomas Eloy Martínez (Anclajes, 2016)
This document analyzes two historical novels belonging to the considerable corpus born out of the trauma of the last military dictatorship in Argentina. In On a Similar Night (2012), Leopoldo Brizuela presents a conflict between filial love and guilt while Tomas Eloy Martínez’s Purgatory (2011) recounts the story of an exiled woman’s efforts to locate her husband who was kidnapped 30 years earlier. The issues of missing loved ones (desaparecidos, in Spanish) and the unfinished mourning they represent are brought to the forefront in these works. The objective of this analysis is to study the narrative strategies employed by both authors faced with the task of narrating a history in which they are indirect or inadvertent protagonists. This is the basis from which I will examine how certain elements (the evocative power of language, dreams as a representational device, and fantasy as a means to bring back the missing) were used to reflect upon the powerof writing when recording trauma as part of a personal and collective duty toward historical memory.
Keywords: Argentine Literature; historic memory; dictatorship; Leopoldo Brizuela; Tomas Eloy Martínez